Association between myocardial triglyceride content and cardiac function in healthy subjects and endurance athletes. - Eiryu Sai (Public Library of Science (PLoS), 2013)
Ectopic fat accumulation plays important roles in various metabolic disorders and cardiovascular diseases. Recent studies reported that myocardial triglyceride (TG) content measured by proton magnetic resonance spectroscopy ((1)H-MRS) is associated with aging, diabetes mellitus, and cardiac dysfunction. However, myocardial TG content in athletes has not yet been investigated. We performed (1)H-MRS and cardiac magnetic resonance imaging in 10 male endurance athletes and 15 healthy male controls. Serum markers and other clinical parameters including arterial stiffness were measured. Cardiopulmonary exercise testing was also performed. There were no significant differences in clinical characteristics including age, anthropometric parameters, blood test results, or arterial stiffness between the two groups. Peak oxygen uptakes, end-diastolic volume (EDV), end-systolic volume (ESV), left ventricular (LV) mass, peak ejection rates and peak filling rates were significantly higher in the athlete group than in the control group (all P<0.02). Myocardial TG content was significantly lower in the athlete group than in the control group (0.60 ± 0.20 vs. 0.89 ± 0.41%, P<0.05). Myocardial TG content was negatively correlated with EDV (r = -0.47), ESV (r = -0.64), LV mass (r = -0.44), and epicardial fat volume (r = 0.47) (all P<0.05). In conclusion, lower levels of myocardial TG content were observed in endurance athletes and were associated with morphological changes related to physiological LV alteration in athletes, suggesting that metabolic imaging for measurement of myocardial TG content by (1)H-MRS may be a useful technique for noninvasively assessing the "athlete's heart".